P143 EDOXABAN EFFECT IN A BREAST CANCER PATIENT WITH LIVER ARTERIAL INFUSION CHEMOTHERAPY (LAIC) AND BOTH JUGULAR VEIN AND HEPATIC ARTERY THROMBOSIS. A UNIQUE CLINICAL CASE. (18th May 2022) - Fioretti, A; Leopizzi, T; Mariangela, P; Fazio, V; Ranieri, G; Luzzi, G; Gadaleta, C; Oliva, S
Abstract: : 41 y–o woman, without cardiovascular risk factors, was diagnosed with breast cancer (pT2N1aMx, G3, ER:70%, PgR:30%, HER–2/NEU:2+, Ki67:60%). Treated (2010) with adjuvant antracyclines, taxanes and hormonal therapy. Subsequently, developed (2012) bone lesions treated with radiotherapy and hepatic metastases (2016) treated with systemic infusions of bevacizumab and taxanes. Started (2017) chemoembolization (CE), due to further liver severe progression configuring a main hepatic disease. Started LIVER ARTERIAL INFUSION CHEMOTHERAPY (LAIC) with 5fluoruracil and concomitant venous systemic chemotherapy (CT) with taxanes and bevacizumab. Developed (2020) arterial catheter–related thrombosis (ACRT) recurrent after urokinase, clopidogrel and enoxaparin, in spite of thromboprohylaxis with aspirin/clopidogrel. LAIC was discontinued and CT with taxanes and trastuzumab was administrated by systemic route. Left jugular deep vein thrombosis (DVT) occured (2021), treated for 8 months with low–molecular–weight heparin (LMWH): firstly with enoxaparin 100 IU/kg twice a day and secondly, because of lack of efficacy and patient's request for a more manageable therapy, with parnaparin 6400 IU once a day. After 8 months the patient refused any more injectable anticoagulant drugs, asking for oral root of administration. LMWH were replaced by direct oral anticoagulant (DOAC), edoxaban 30 mg/die (weight: 43 kg). After 3 months of edoxaban a duplex ultrasound showed an almost total DVT regression; neither bleedings nor dru–drug interactions with the ongoing CT were detected. Instead, the 3 months follow–up CT–scan revealed persistence of the ACRT, despite of edoxaban. Conclusions: Thromboembolism is the second leading cause of death in malignancy. Venous thromboembolic events are prevalent compared to the arterial ones. However, in active cancer hypercoagulable burden is common to both kind of thrombosis and sometimes occur simultaneously. In this case, a young woman with advanced breast cancer treated with CE and LAIC developed both DVT and ACRT. According to inefficacy and patient's preference, we replaced LMWH with edoxaban. Arterial thrombosis was persistent although treated with several antithrombotic agents, whereas edoxaban resulted effective in the DVT regression. The take home message of this case report is that DOACs could be a feasible, efficient and safe anticoagulant choice for venous cancer related thrombosis.